2021
DOI: 10.1093/jxb/erab311
|View full text |Cite
|
Sign up to set email alerts
|

Two citrus KNAT-like genes, CsKN1 and CsKN2, are involved in the regulation of spring shoot development in sweet orange

Abstract: Shoot tip abortion is a very common phenomenon in some perennial woody plants that affects the height, architecture, and branch orientation of trees. To date, little is known about the mechanism of shoot tip abortion. In this study, a sweet orange gene encoding a KNAT-like protein (CsKN1) was identified and showed high expression in the shoot apical meristem (SAM). Overexpression of CsKN1 prolonged the vegetative growth of SAM, and silencing of CsKN1 resulted in the loss or inhibition of SAM in transgenic plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Interestingly, CiKN1 interacts with CiKN6. A recent report also showed that CiKN1 interacted with another KNOX protein (CsKN2) and was involved in the development of sweet orange spring shoots (Zeng et al., 2021). Until now, little has been determined regarding the interactions between KNOX family protein members.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, CiKN1 interacts with CiKN6. A recent report also showed that CiKN1 interacted with another KNOX protein (CsKN2) and was involved in the development of sweet orange spring shoots (Zeng et al., 2021). Until now, little has been determined regarding the interactions between KNOX family protein members.…”
Section: Discussionmentioning
confidence: 99%
“…Ciclev10015581m showed high homology with Arabidopsis STM among six the KNOX genes. In Arabidopsis and citrus, STM does not have a strong autonomous function in promoting leaf dissections because its activities are mainly limited to SAM and inhibited in lateral organs (Hay & Tsiantis, 2006; Zeng et al., 2021; Zhang et al., 2020). Ciclev10008269m showed high homology with KNAT3 of Arabidopsis and Medicago truncatula , and involved in the development of embryo sac and symbiotic nodule organ (Di Giacomo et al., 2017; Pagnussat et al., 2007).…”
Section: Morphological and Transcriptome Analysis Of Citrus Leaf Deve...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several citrus genes that control traits of interest have been cloned and characterized as novel targets for cis and intragenesis approaches. Between them CsSAMT1 ( Salicylic acid Carboxyl Methyltransferase 1 ), which confers tolerance to HLB; CsMADS5, a fruit ripening-associated transcription factor, that positively regulates carotenoid biosynthesis in citrus; a CsMYB96 transcription factor, which enhances citrus fruit resistance against fungal pathogens; CiMADS43, a MADS-Box gene involved in citrus flowering and leaf development and CiNPR4, an NPR1-like gene that enhanced resistance of transgenic citrus plants to HLB ( Li et al, 2020 ; Khan et al, 2021 ; Lu et al, 2021 ; Peng et al, 2021b ; Zeng et al, 2021 ; Zhang et al, 2021 ; Zou et al, 2021 ).…”
Section: Emerging Technologies: Cis and Intragenesis Trans -Grafting And Gene Editing In Citrusmentioning
confidence: 99%